Rare combination of simple virilizing form of 21-hydroxylase deficiency, Graves' disease and 47, XXX in a woman: A case report. Issue 43 (28th October 2022) - Liang, Dong; Han, Minmin; Xu, Linxin; Ren, Yi; Zhang, Yi; Yin, Jianhong; Yang, Jing; Liu, Yunfeng
Abstract : Rationale: Coexistence of congenital adrenal hyperplasia due to 21-hydroxylase deficiency, Graves' disease and 47, XXX is rare. We report a case of a 25-year-old woman presented with masculine appearance, hirsutism and enlarged clitoris. Lab tests showed elevated serum 17 hydroxyprogesterone, testosterone, dehydroepiandrosterone. Gene test revealed heterozygous gene mutation in CYP21A2:NM_000500:exon4:c.518 T > A, NM_000500:exon8:c.C1024T. Karyotype analysis showed 47, XXX. After prednisone replacement and antithyroid therapy, she got a normal menstruation and normal level of testosterone. These findings demonstrate that patients with abnormal chromosome are likely to combine 21-hydroxylase deficiency (21-OHD), thus karyotyping test should not be neglected for those who have been already diagnosed as 21-OHD. Additionally, chromosomal abnormality such as 47, XXX and Turner syndrome had susceptibility to develop autoimmune thyroid disease because a gene on X chromosome may be responsible for the occurrence of autoimmune thyroid disease. Moreover, both 21-OHD and Graves' disease (GD) can lead to high level of testosterone, thus we should keep in mind to test chromosome and thyroid function in 21-OHD patients to avoid misdiagnose or missed diagnosis. To the best of our knowledge, this is the first report of simple virilizing (SV) 21-OHD patient combined with 47, XXX and Graves disease. Patient concerns: A 24-years-old female of Han ethnicity was admitted to the endocrinology department complaining of absence of menses for half a year. The patient didn't noticed her enlarged clitoris until she was 17 years old. Her menarche was 16 years old and the final height was 163 centimeter. She was diagnosed with GD 2 months before admission to our hospital due to palpitation, heat intolerance, muscle weakness. Diagnoses: The patient was diagnosed with SV 21-OHD, Graves disease and 47, XXX. Interventions: At first, the patient was given 10 mg methimazole twice a day as well as 5 mg predisone in the morning and 2.5 mg in the evening. After a year of regular medication and reexamination, she got a regular menstruation and thyroid function and now is taking 2.5 mg prednisone twice a day. Outcomes: The patient got a regular menstruation and thyroid function. Laboratory results showed: testosterone declined to 0.1nmol/L (0.1–1.67nmol/L) and 17 hydroxyprogesterone get back to normal level: 1.01ng/ml (0.30–2.34ng/mL). However, her enlarged clitoris has not narrowed. Lessons: Patients with abnormal chromosome are likely to combine 21-OHD, thus karyotyping test should not be neglected for those who have been already diagnosed as 21-OHD. Additionally, chromosomal abnormality such as 47, XXX and Turner syndrome had susceptibility to develop autoimmune thyroid disease because a gene on X chromosome may be responsible for the occurrence of autoimmune thyroid disease. Moreover, both 21-OHD and GD can lead to high level of testosterone, thus we should keep in mind to test chromosome and thyroid function in 21-OHD patients to avoid misdiagnose or missed diagnosis. To the best of our knowledge, this is the first report of SV 21-OHD patient combined with 47, XXX and Graves disease.